2020
DOI: 10.1371/journal.pone.0239754
|View full text |Cite
|
Sign up to set email alerts
|

Trend and determinants of complete vaccination coverage among children aged 12-23 months in Ghana: Analysis of data from the 1998 to 2014 Ghana Demographic and Health Surveys

Abstract: Background Vaccination is proven to be one of the most cost-effective measures adopted to improve the health of children globally. Adhering to vaccines for children has the propensity to prevent about 1.5 million annual child deaths globally. This study sought to assess the trend and determinants of complete vaccination coverage among children aged 12-23 months in Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
7
25
1
Order By: Relevance
“…The results confirm those of other studies which found consistent associations between maternal characteristics and childhood vaccination. 41 46 49 50 As found in other studies, 33 41 46 exposure to mass media should be emphasised due to its significant positive association with complete vaccination. As a result, well-crafted and tailored information and sensitisation programmes and messages should be disseminated through radio stations, newspapers and television stations based on the positive outcomes from other studies.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The results confirm those of other studies which found consistent associations between maternal characteristics and childhood vaccination. 41 46 49 50 As found in other studies, 33 41 46 exposure to mass media should be emphasised due to its significant positive association with complete vaccination. As a result, well-crafted and tailored information and sensitisation programmes and messages should be disseminated through radio stations, newspapers and television stations based on the positive outcomes from other studies.…”
Section: Discussionmentioning
confidence: 62%
“…This result confirms the association between PNC attendance and full or complete childhood vaccination as found in several studies. 33 38 42 47 It seems possible that the results could be attributed to the fact that early PNC provides an avenue to initiate vaccines such as BCG, Diptheria, Pertussis and Tetanus (DPT) and polio, which could later enhance compliance with the immunisation programme and also an opportunity to initiate vaccination among those not immunised. 47 Another possible explanation could be that during PNC, mothers are educated and counselled on the importance of immunising their children against vaccine-preventable diseases and deaths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a qualitative study by Jalloh et al [15] indicates that perceived beliefs about the side effects coupled with concerns about receiving multiple vaccines on the same day were signi cant barriers to the uptake of childhood vaccination and its coverage. Also, other studies from Ghana [16] and Nigeria [17] suggest that urban residency and higher maternal education are associated with higher likelihoods of complete childhood vaccination coverage.…”
Section: Introductionmentioning
confidence: 92%